Pedagogy: A Rebellious Discipline. Boundaries of a Debate and Its Ethical- Political Perspectives - Juan Rafael Gómez-Torres (Universidad Nacional, Costa Rica, 2016)
The present study aims to develop a rupture of the classical linear matrix about the concept of pedagogy. The proposal restates the idea of pedagogy within an interconnection of different perspectives and knowledge about reality as well. In order to reach that, the vision of pedagogy as a rebellious discipline is proposed. The colonialist and separatist boundaries that characterize pedagogy are discussed. Therefore, the concept of indiscipline as an alternative which resists the educational system is presented, and the new idea of pedagogy as an act of thinking-feeling-doing is analyzed.